Challenging conventional approaches to managing wastewater use in agriculture - Huibers, F.; Redwood, M.; Raschid-Sally, Liqa (2010)
In developing countries urban wastewater management often fails to cope with increasing wastewater generation. Financial, technical and institutional limitations force authorities to discharge substantial amounts of untreated or partially treated wastewater into surface waters. Consequently, uncontrolled use of polluted water is increasingly common in the downstream peri-urban areas. Although wastewater use bears a significant risk on human health, such use is also productive and an asset for many. Agricultural use of wastewater is a strong manifestation of the urban-rural connection and transfers a waterborne risk from the wastewater disposal system to the food chain, requiring a paradigm shift in the approaches applied to risk minimization. Conventional models for urban wastewater treatment and management are based on top-down, mechanically driven approaches that do not, or do not sufficiently, consider the links between the social, economic and health aspects. This situation is understandable from historical and technological points of view, but does not provide innovative solutions to current problems in developing country cities. A different approach is required, one that rethinks conventional wastewater system design and management. By adopting a systems approach to analysing both the water and food chains, one discovers the interactions of different stakeholders that treat and use (or abuse) water, the impacts on overall productivity and the risks. Governance systems to manage wastewater use in agriculture must incorporate decentralization to accommodate thinking at the bottom layer, encourage stakeholder engagement and provide coordination and policy cohesion for managing risks jointly from both the water and food chains.